Design of Underground Belt Transportation Control System of Metal Mine and Its Applicatio - ZHANG Tian-hong; JI Chun-shan; ZHU Wen-ju (Gong-kuang zidonghua, 2011)
In view of problem of bad reliability that original belt transportation system of one metal mine is controlled by relay, the paper proposed a reform scheme of belt transportation control system based on ControlLogix technology. The system uses ControlLogix technology to realize any combination of driving and motion control of belt transportation system; it uses fiber communication and network redundancy technology to realize functions of device configuration, data collection and remote fault diagnosis; it uses electronic overload relay to realize protection for motor; it uses visual man-machine interface to realize real-time monitoring and control for working state of belt transportation system. The actual application showed that the system improves reliability of belt transportation system.